Legal Aspects of Cooperation Agreement on Cultivation of Siwalan Orchard Land in Sumenep Regency - Sumriyah, Sumriyah; Jusmadi, Rhido; Hadi, Rusman; Khofifah, Linda Uril (Law Development Journal, 2025)
Based on the provisions of Article 1313 of the Criminal Code that an agreement is binding on both parties like a law, meaning it gives rise to rights and obligations for the parties who make it, because basically every agreement must be kept. One of the agreements that have long existed in the community is a plantation land management agreement in the form of a cooperation agreement implemented in the village of Pragaan Daya, Pragaan District, Sumenep regency for the cultivation of siwalan orchard land. In this journal applies the method of empirical juridical approach, namely legal research that obtains its data from primary data or data or data obtained directly from the public in this study found some applications that have not been in accordance with applicable legal rules where in its application, the form of agreements that should be made in writing but only made orally. This is due to the lack of human resources in the field of employment and the desire of the landowner himself to make a work agreement for a certain time orally, given the existence of this written agreement can certainly provide legal certainty to siwalan workers, especially if later when in the field something happens that can harm them, they can ask for the work Agreement and the result of the violation of the agreement that occurred in the cooperation agreement called default can be resolved amicably, non-litigation or litigation.